Mandibular positioning devices for the control of snoring - Stradling, JR; Negus, T; Langford, B; Smith, D (1996)
Patients complaining of antisocial snoring have few options available to them of proven efficacy. There are a plethora of 'gadgets', most having no evidence to justify their appearance on the market. Surgery, such as uvulopalatopharyngoplasty, is an option but many patients do not feel that the pain, risks, and unpredictability of this operation are justified. Oral devices worn at night, to hold the lower jaw forward, have recently been shown to help mild to moderate obstructive sleep apnoea (OSA). There are no controlled studies on the use of such devices for the management of antisocial snoring. 14 snorers with no evidence of significant OSA on their diagnostic study, already established on oral appliances for the control of snoring, participated in this study. They were studied overnight at home on two occasions, using a portable device (RM50, Parametric Recorders) on the third consecutive night sleeping either with, or without, their oral devices (in randomised order). Snoring (using a throat microphone), oxygen saturation, posture, and indirect beat to beat blood pressure were measured. The latter (using pulse transit time) provided an index of 'autonomic arousals' as well as a measure of respiratory effort. In all but one of these highly selected patients, the oral devices clearly reduced the amount of snoring (P<0.006) from an average of 205(SD147) to 68(SD80) snores/hour (maximum number about 900/hr with a respiratory rate of 15/min). There were no significant overall changes in respiratory effort, arousals or >4%SaO2 diprates. These patients represent only those who were able to tolerate the appliance, and we do not know how many snorers referred for the provision of such devices use them long term. However, with such clear evidence of their potential efficacy, and no suggestion from other studies of any harm, it would seem reasonable to introduce this approach into the management of antisocial snoring.